PEMBERDAYAAN MASYARAKAT DESA BRUMBUNG, KABUPATEN KEDIRI, MELALUI PROGRAM PENDAMPINGAN PENDIDIKAN DAN PELESTARIAN WARISAN BUDAYA - Yuwono, Ardi Tri; Budianto, Agus; Widiatmoko, Sigit; ., Yatmin; Budiono, Heru; Afandi, Zainal; Braake, Gijsbert ter (ABDI MAKARTI, 2026)
Schools and cultural heritage need to be strengthened in supporting the achievement of the Sustainable Development Goals (SDGs), including through cultural preservation and cultural heritage management. This community service activity in Brumbung Village aims to increase literacy awareness and make a positive contribution to the development of education and the preservation of local cultural heritage. By applying the Asset-Based Community Development (ABCD) method, this program utilizes local assets such as the Patirtan Geneng Site, the Brumbung Small Museum, and basic education institutions. A series of activities were carried out, including clean-up actions of cultural heritage sites and museums, teaching and socialization of culture-based curriculum, socialization of cultural heritage preservation, and Wayang Kulit performances. The results show a significant increase in people's awareness and knowledge, which has an impact on changing their attitudes and behaviors towards cultural heritage. This activity also strengthens the understanding that cultural preservation is the collective responsibility of the community, not just the government or formal institutions. Thus, this program becomes an effective model for local asset-based community empowerment in order to support sustainable education and cultural preservation.